All-Russian Conference on Spondyloarthritis in the 21st Century, dedicated to the occasion of the 75th birthday of I.G. Salikhov (Kazan, 21–23 April, 2016) (Научно-практическая ревматология)
All-Russian Conference on Spondyloarthritis in the 21st Century, dedicated to the occasion of the 75th birthday of I.G. Salikhov (Kazan, 21–23 April, 2016).